How can we hold the powerful to account in Africa when the ruling party acts with impunity and disregards the will of the voters? Living Rights Festival - Levy, Moira (New Agenda: SA Journal of Social and Economic Policy, 2025)
Many countries call themselves democracies simply because they hold regular elections. At a panel discussion in October 2024 as part of IFAA’s Living Rights Festival, participants were reminded that elections are a necessary but not sufficient requirement for democracy. A key question that surfaced in the debate, titled “Holding the Powerful to Account in Africa,” was what actions could promote accountability in a so-called “democracy” in which the ruling party is able to act with impunity and disregard the will of the voters?